Vaginal candidiasis diagnosis and treatment in gynecological practice - Soihet, Samoel (2015)
The effective treatment of vaginal candidiasis has become a social and therapeutic problem, because it is a very annoying disease but not life, committed the happiness of married life. The use of conazoles in any form in the present, is a solution. But the problem of recurrences severely frustrate the results, so it is necessary to control, treat prefisponentes factors for failure or recurrence. Keep in mind that the sexual factor in the couple is involved, it must be considered in parallel therapeutic, and all care to prevent infestation. With the advance of anti fungal pharmacology, while we consider how to create defense against Candida vagina is not achieved, it will continue invading. Therefore, good technique is used prophylactically local treatment, preferably, or in the future, the single oral dose to prevent reinfection.